Synthesis and characterization of spermidine containing sulphur - Sahabudin, Adzly Hairee; How, Fiona Ni Foong; Abdul Ghani, Radiah (Penerbit UMT, Universiti Malaysia Terengganu (UMT), 2016)
Studies in compound containing sulphur and the polyamine transport system is beneficial in oncology as both affect cancer cells. Compounds containing sulphur such as organosulphur are known for their anti-cancer properties. The polyamine transport system however is known for its ability to interact with cancer cells directly. By adding sulphur to known natural polyamine, the resulting compound is anticipated to retain both properties. One of the widely used of polyamine moiety is used as the cell delivery vector to transport sulphur to the targeted cancer cells. In this study, the spermidine containing sulphur was synthesized by adding carbon disulphide atoms to spermidine atom. The compound was then characterized and analyzed to determine its physiochemical properties and chemical structure. Determination on the characteristic and chemical structure of the compounds were carried out using various techniques such Fourier transformed infrared spectroscopy, thin layer chromatography and gas chromatography mass spectroscopy.